Mechanical characterization and testing of multi-polymer combinations in 3D printing - Ana María Gómez Amador; Ricardo Andre Venturini Avendano; Alejandro Quesada González; Leopoldo Prieto Fernández (Heliyon)
One of the key advancements brought on by Industry 4.0 is additive manufacturing, particularly material extrusion printers that enable the creation of complex parts using composite materials. This article presents a study on the mechanical behavior of 3D printing multi-materials, which are easily accessible and cost-effective for users. Tensile, compression, and flexural tests were conducted on various material configurations to explore their mechanical properties. Results indicate that certain material combinations exhibit enhanced properties in tension and compression, while individual materials perform stronger in flexural tests due to improved interlayer adhesion.The research highlights how material combinations in 3D printing can impact the mechanical properties of parts, offering potential applications in structural design. The study found that a combination of PETG and PLA yields optimal mechanical properties in tensile tests, while configurations with PLA on the outer layer perform best in compression tests. It also identifies a limitation in flexural testing dimensions, where specimens with a 4 mm thickness restrict the possibilities of material combination tests.